Infancia y adolescencia: de los tiempos de socialización sometidos a constricciones múltiples - Lahire, Bernard (Revista de Antropología Social, 2007)
Childhood and adolescence are life periods neglected by sociologists. However, time of primary socialization and the first stages of secondary socialization are constitutive times of primary mental and behavioral dispositions which are going to influence individuals durably. A research based on a long series of case studies shows that it is a time of multiple socialization when conjoined, and sometimes contradictory, influences of family, friends and school makes it felt. Thinking sociologically children and teenagers suppose to catch their place into the different contexts –family, group of friends, school– instead of defining them exclusively by a so-called « youth culture ». In its conclusion, the article concludes emphasizing the risks of research objects parcelling: dividing excessively the problems he is studying –school, family, leisure, culture, media, sociability, etc.–, sociologist has no chance of understanding the specificity of juvenile situations.